Triazolopyrimidine Derivatives: A Comprehensive Review of Their Synthesis, Reactivity, Biological Properties, and Molecular Docking Studies - Mrayej, Hajar El; En-nabety, Ghizlan; Ettahiri, Walid; Jghaoui, Mohamed; Sabbahi, Rachid; Hammouti, Belkheir; Rais, Zakia; Taleb, Mustapha (Universitas Pendidikan Indonesia, 2025)
Triazolopyrimidines are heterocyclic compounds with a unique structure and a wide range of applications in medicinal chemistry. The versatility of the triazolopyrimidine scaffold allows for the exploration and development of compounds with diverse pharmacological properties. This literature review encompasses the period from 2014 to 2022 and offers a comprehensive and inclusive overview of the synthesis, reactivity, and biological properties studies of triazolopyrimidines. The review summarizes the various synthetic methods used to prepare triazolopyrimidines and their reactions with different reagents. It also examines their pharmacological properties, such as anti-COVID-19 and anticancer effects, and their molecular docking analysis with relevant targets. The review aims to contribute to a better understanding of the potential applications of triazolopyrimidine in the field of medicinal chemistry. This literature review from 2014 to 2022 provides a comprehensive exploration of triazolopyrimidines, highlighting their diverse applications in medicinal chemistry. The review aims to offer a thorough understanding of triazolopyrimidines' versatility, serving as a valuable resource for advancing drug development in medicinal chemistry.